A dimensão do estudo da ética no ensino médio técnico: uma abordagem com base nos profissionais de educação do IFAM/campus Humaitá-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The paper presents a study about the conceptualization of ethics in the teaching-learning process, addressing the main aspects related to training, knowledge and teaching practices, with the scope of evaluating the role of ethics and analyzing the degree of importance given to the subject by the educational institutions, specifically with regard to Technical High School, due to the proximity of the students in coming of age. It is necessary to know about the role of the teacher, as well as the students interest in the subject. The research proposes to observe about the learning about the ethical precepts, and intends to verify on the need to stimulate the students to the critical thinking on the subject. It is also necessary to recognize the essential contact with the concepts and rationale attached to ethics. The research resulted in the identification of the importance of ethics in the discussions inside and outside the classrooms, given their social relevance to current issues. The research was developed under the focus of dialectics and historical materialist reading, because it brings to light the essence of critical thinking stimulated by Karl Marx, who defended the development of research through interdisciplinary criticism in which philosophical, historical, sociological problematizations , political, legal and economic, having been developed from the qualitative approach, involving an investigation of a descriptive and theoretical nature. The subject of the research presupposes discussion under both historical and philosophical perspectives of ethics, which made it imperative to walk a course in the face of the construction of its concept in time with the need to approach the understanding of some authors of their own philosophical position, such as Socrates, Plato, Aristotle, Thomas Hobbes, Dermeval Saviani, among many others.
The dimension of the study of ethics in technical medium education: an approach based on IFAM/campus Humaitá-AM educational professionals
Keywords: Ética no ensino; Ensino Médio Técnico; Aluno; Professor; Aprendizagem; Profissionais de educação do IFAM; Ethics; Technical high school; Student; Learning; IFAM education professionals; Teacher; CIÊNCIAS HUMANAS